Nosotros y la naturaleza: Dar y recibir - Narice, Rosana; Pinto, Héctor; Alegre Cobach, Andrea; Vázquez, Beatriz (Revista Aves Argentinas, 1998)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).